2012
DOI: 10.1080/07055900.2012.733307
|View full text |Cite
|
Sign up to set email alerts
|

Iceberg Detection Using Compact Polarimetric Synthetic Aperture Radar

Abstract: In recent years, the use of synthetic aperture radar (SAR) for iceberg detection has been increasing thanks to the greater availability and coverage of SAR data, particularly polarimetric data. Greater amounts of polarimetric information can increase detection performance, preventing false alarms and missed detections. However, quad-polarization (quad-pol) SAR systems have increased data rate and power usage requirements, causing quad-pol modes to have generally half the swath width of dual-polarization (dual-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Icebergs are pieces of freshwater ice calved from glaciers or ice shelves. They are natural ocean hazards to ships and maritime activities [1,2]. Climate change is increasing the formation of new icebergs due to rapid melting and speeding up of glacial ice [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Icebergs are pieces of freshwater ice calved from glaciers or ice shelves. They are natural ocean hazards to ships and maritime activities [1,2]. Climate change is increasing the formation of new icebergs due to rapid melting and speeding up of glacial ice [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Compact polarimetry has also been applied to other ocean applications, like ship detection 20 and iceberg detection. 21 During the last years, substantial research have been done on developing methods for detection and monitoring of oil spill at sea in synthetic aperture radar (SAR) images. 22 However, operational services like EMSA's CleanSeaNet does not currently provide the user with estimates of oil spill characteristics, like type or thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the reconstructed pseudo covariance matrix is similar to the FP covariance matrix. Recently, CP SAR data has been used for ocean target detection [7], [10].…”
Section: Introductionmentioning
confidence: 99%